Peran Mediasi Dogmatisme dalam Hubungan antara Need for Closure dan Intellectual Humility - Irsal Harifasyah; Sianipar, Agnes (Journal of Research and Measurement in Psychology: JPPP, 2024)
The role of Intellectual Humility (IH) - an awareness of the limits of one's knowledge - is crucial in fostering meaningful social interactions and dialogues within pluralistic societies. Previous research found that people who need quick answers and avoid ambiguous situations or different opinions (known as individuals with high Need for Closure, or NFC) also have low IH. However, there are also studies that do not find a significant relationship between NFC and IH. Therefore, this study aimed to investigate to what extent NFC could predict IH and whether being dogmatic played a mediating role in the relationship of NFC and IH. We surveyed 232 individuals aged 17–70 years (mean age = 30.69, SD = 10.98, 55.6% female), administering the NFC, IH, and Dogmatism scales. Our mediation analysis, employing PROCESS Model 4, revealed that while NFC did not directly predict IH, it indirectly predicted IH through the full mediation of individual dogmatism. This finding underscores the critical role of dogmatism as a factor that can be targeted to enhance IH. Discussion of the findings of this research will emphasize the importance of a deeper understanding of factors that can reduce dogmatism in the future to improve IH and consequently, the quality of social discourse in pluralistic societies.